The Phenomenon of Mask Dance in East Asia from the Lens of Dance Teachers - Teng, Yue (International Journal of Social Sciences and Public Administration, 2024)
This paper explored the phenomenon of mask awareness in East Asian dance from the perspective of dance teachers in Shiyou Village, Jiangxi Province, China. It aimed to determine the evolution of mask dance, explore the cultural influences of East Asian dances on the mask dance, and examine the significance of mask dance in dance education from a cultural perspective. A qualitative research design was used, involving interviews with four experienced dance teachers to collect their views and experiences on mask dance. The interviews were transcribed, analyzed thematically, and corroborated with literature research. The study revealed the cultural symbols, meanings and functions of mask dance in East Asia. It highlighted the role of mask dance in preserving cultural heritage, enhancing social cohesion, promoting cross-cultural understanding, and stimulating artistic innovation. The paper provides useful insights for dance practice and cultural heritage in the region.